THE EFFECT OF GINGER ON NAUSEA AND VOMITING IN PREGNANT WOMEN IN THE FIRST TRIMESTER - Ulpawati Ulpawati; Silvia Mona; Susanti Susanti (Jurnal Kesehatan, 2021)
Hyperemesis gravidarum is characterized by extreme nausea and vomiting during the first trimester of pregnancy. It is different from regular morning sickness in that it might cause dehydration and hunger. One of the pretest-posttest groups is used in this study, which employs a quasi-experimental research approach. This study included first-trimester pregnant women who reported nausea and vomiting more than three times per day. With 16 responders, the sampling strategy employed was incidental sampling. The data were analyzed using univariate and bivariate analyses using a dependent t-test. The intervention took the form of a ginger infusion made with 250 mg of red ginger, 500 ml of water, and 50 grams of brown sugar as a sweetener, which was then boiled and sipped warm every morning and evening for 14 days. The ginger drink was provided by the researchers. The respondent consumed the ginger drink in the morning and evening, as indicated. Every two days, calls are placed to determine the frequency of nausea and vomiting. Before treatment, average nausea and vomiting in first-trimester pregnant women were 3.87, with a standard deviation of 0.342. Average nausea and vomiting in first-trimester pregnant women after ginger infusion treatment was 1.19, with a standard deviation of 0.403. Giving boiled ginger water reduces nausea and vomiting in pregnant women in Trimester I with a p-value = 0.000 (p-value = 0.05). Pregnant women can use ginger water decoction, which has been shown to be useful in lowering nausea and vomiting, which are common throughout pregnancy.